Honeypots: Why We Need A Dynamics Honeypots? - Budiarto, Rahmat; Samsudin, Azman; Chuah, Wee Heong; Noori, Salah (2004)
Honeypots has emerged to become a great tool for administrator to track down the intruder, prevent attack by intruder and log all the activity done by the intruder.